2007
DOI: 10.1371/journal.pone.0001154
|View full text |Cite
|
Sign up to set email alerts
|

DNA Barcoding in the Cycadales: Testing the Potential of Proposed Barcoding Markers for Species Identification of Cycads

Abstract: Barcodes are short segments of DNA that can be used to uniquely identify an unknown specimen to species, particularly when diagnostic morphological features are absent. These sequences could offer a new forensic tool in plant and animal conservation—especially for endangered species such as members of the Cycadales. Ideally, barcodes could be used to positively identify illegally obtained material even in cases where diagnostic features have been purposefully removed or to release confiscated organisms into th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
248
2
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(271 citation statements)
references
References 38 publications
17
248
2
4
Order By: Relevance
“…Others explained amplification failure as a result of poor annealing with standard matK or rbcL primers and highlighted the need to redesign species‐specific primers (Kress & Erickson, 2007; Sass et al. 2007; Fazekas et al., 2008; Lahaye et al., 2008; Casiraghi et al., 2010; Roy et al., 2010). According to Casiraghi et al.…”
Section: Discussionmentioning
confidence: 99%
“…Others explained amplification failure as a result of poor annealing with standard matK or rbcL primers and highlighted the need to redesign species‐specific primers (Kress & Erickson, 2007; Sass et al. 2007; Fazekas et al., 2008; Lahaye et al., 2008; Casiraghi et al., 2010; Roy et al., 2010). According to Casiraghi et al.…”
Section: Discussionmentioning
confidence: 99%
“…Gymnosperms are seed bearing plants comprises an important four subclasses such as cycadidae, Gingoidae, Gnetidae and Pinidae, representing 12 families, 83 genera and about 990 species (28 (29). Recently universality of 9 potential matK and 1 rbcL primers were assessed for barcoding gymnosperms (30).…”
Section: Dna Barcoding Of Gymnospermmentioning
confidence: 99%
“…However, the NJ tree indicated that the species with different higher-level phylogenies, such as the subgenus and the genus (the outgroup), can be distinguished. Numerous other studies also suggested that rbcL is only suitable for DNA barcode at the genus level (and above) (Kress and Erickson, 2007;Newmaster et al, 2006;Sass et al, 2007).…”
Section: Applicability Of the Candidate Chloroplast Dna Barcodesmentioning
confidence: 99%
“…However, it is not an ideal marker because of the overlap between interspecific and intraspecific variations. In addition, the long length, poly-G, poly-C, and poly-A resulted in the difficulty of sequencing and sequence analysis (Sass et al, 2007). Although we used a cloned single-copy to sequence, senior structures appeared in some samples; thus, sequences were performed twice or thrice.…”
Section: Applicability Of Nritsmentioning
confidence: 99%
See 1 more Smart Citation